Pengaruh Pelatihan, Motivasi, Disiplin dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Cahaya Optima Karya Jakarta Pusat - Sylvia Nur Saputri; Purnadi Purnadi; Hengky Widhiandono; Restu Frida Utami (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Employee performance plays a fundamental role in determining the achievement of corporate targets, making effective human resource management a necessity. In this context, PT Cahaya Optima Karya is still faced with several strategic problems, namely training programs that are not comprehensively structured, levels of motivation and work discipline that need to be improved, and the contribution of the work environment that is not optimal in driving productivity. The research method applied is quantitative. The sampling technique uses a census, where questionnaires are distributed to the entire employee population of 113 people. Furthermore, the collected primary data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach operated through the Smart PLS 3 application. The results of the hypothesis testing indicate that the variables of motivation and work discipline have a positive and significant effect on employee performance. Although showing a positive direction of influence, the variables of training and work environment were not proven to be statistically significant.